HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN PERILAKU ANAK DI TAMAN KANAK-KANAK PGRI KECAMATAN NGEBEL, KABUPATEN PONOROGO - Sumy DwiAntono, Sumy DwiAntono; Dwi Estuning Rahayu, Dwi Estuning Rahayu (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2013)
Pattern brings upo behavior at apllied in child and has relative consistent from time to time.Children under five age is critical period or â edden periods â so thatÂ pattern will bring up disagree with child need will causes impact unfortable. Base on this research aim the mentioned detects relation between pattern bring up parents with child behavior at TK PGRI Kecamatan Ngebel, Kabupaten Ponorogo. This research is analytic research with plan â Cross Sectional â as to population old everbody and child at TK PGRI KecamatanNgebel that number 40 childs. Sample at take with technique â Simple Random Sampling â amount of 36 brespondents. Data collecting by admission filling quissonaaire to detect pattern kidsÂ bring up and use data sekunder shaped child development evaluation summary TK to detect child behavior. Data processing uses computer and with statistic teskoefisien kontingention with literatil on level P < 0,05. The research result shows that parens age characteristic in age group 40 â 49 year amount ofÂ 42 %.Parents education level a large part elementary school that amountÂ 39 % and parents job a large part farmer amountÂ 33 % .Pattern bring up parents Consists of authoritarian amount of 8 %,Permisif 64 % and Democratics 28 % child behavior distribution consists of good amount of 33 % enough (want guidance ) amountÂ of 67 %. Haven does error standard 5% (0,05) so P counted > 0,05 mean to accepted and H1 at refuse.Conslution : Not found relation between pattern brings up parents with child behavior at bursary school.Keywords : pattern brings up parents, child behaviorÂ